Finite size effects in ferroelectric nanosystems: Absence of mode softening - D. Wolpert; W. Cox; J. Cerne; A. Markelz; T. Zhao; R. Ramesh (2003 Nanotechnology Conference and Trade Show - Nanotech, 2003)
We present measurements of the mode softening behavior for PbZr 0.5Ti0.5O3 (PZT(50)) thin films using terahertz time domain spectroscopy (TTDS). The films were grown using pulsed laser deposition (PLD) techniques on silicon substrates to study how reduced size affects the mode softening behavior. At room temperature two modes are observed at 1.1 THz (37 cm-1) and at 2.3 THz (77 cm-1). As the temperature is increased toward Tc we do not see strong mode softening, but rather a spectral weight transfer from the high frequency mode to the low frequency mode. This absence of mode softening is more dramatic than that reported by other investigators[1]. We will discuss the possible sources for this discrepancy. These results suggest a change in lattice dynamics for nanoscale ferroelectric films that may be highly dependent on the sample preparation technique.
Keywords: Ferroelectric materials; Fourier Transform Infrared Spectroscopy; Frequency ranges; Lead compounds; Mode softening; nanostructured materials; Natural frequencies; Optical modes; Permittivity; phase transitions; phonons; Routers; Thermal effects